Derivados financieros en Colombia y la nueva regulación de colaterales (2020)
The Colombian derivatives market has grown in the past 20 years. Since the past financial crisis, especially in 2008 with the crash bubble in the USA affected in different ways the financial market. Different contracts are used for derivatives in the Colombian market such as Forwards, Swaps, Futures, and Options. These contracts are negotiated in the OTC (Over The Counter) and in the standardized market. OTC trades directly between two parties and without central exchange or broker; Whereas the standardized market which operates with a broker-dealer or central exchange. It is often found that there can be a breach or an inequality between the parties due to the changing factors of the environment. Therefore, the " Capitulo 18 Circular Basica Contable de la Superintendencia Financiera" was created in Colombia as a new regulation to prevent an imbalance between both parties. Due to the importance of the derivatives market in the world, different countries have implemented this kind of regulation such as the Dodd-Frank and Emir executed by the USA and UE respectively.